Spark plasma sintering of structure‐tailored ultrahigh‐temperature components: First step to complex net shaping. Issue 2 (23rd May 2018) - Wei, Xialu; Izhvanov, Oleg; Back, Christina; Haines, Christopher D.; Martin, Darold G.; Vecchio, Kenneth S.; Olevsky, Eugene A.
Abstract: The net‐shaping capability in spark plasma sintering (SPS) of ultrahigh‐temperature ceramics has been explored in this study. The annular or ring‐like shape is considered here as the first step to a more complex geometry compared to a solid cylinder or disk. ZrC powders have been SPS processed in specially designed graphite tooling to achieve the annular shape geometry. Experimental runs have been carried out to determine the optimal processing parameters for producing highly dense ZrC specimens in this geometry. Finite‐element modeling framework has been constructed to determine the internal stress evolution, as well as densification, during the SPS of the annular‐shaped ZrC. The formulated processing schemes for ZrC have been adapted to process SiC/ZrB2 composite powder with the purpose of making tooling components for SPS applications. The applicability of the obtained composite SPS tooling has been evaluated at high temperature and high pressure associated with SPS regimes.